(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
Tocra is a coastal city located in the northeastern part of Libya, under the Bakur Cliff, It is characterized by an open rocky beach, The main objective of this research is to select Tocra beach for the purpose of collecting and identifying three species of red algae: Corallina ofﬁcinalis and Laurencia Obtusa and Wrangelia penicillata, Comparing this study with previous studies to determine the presence and distribution of these species on Libyan beaches revealed that Corallina ofﬁcinalis was recorded on the beaches of Benghazi, Sabratha, and Zawiya. Comparing the current study with the previous study on Tocra Beach revealed that the same species was recorded in the current study, in addition to another species recorded in the previous study Corallina granifera, Laurencia obtusa was recorded on the beaches of Tripoli, Sorman, Sabratha, Benghazi, Tocra, Derna, and Sousse. Comparing the current study with the previous study on Tocra beach revealed that the same species was recorded in the current study, in addition to the presence of three other species recorded in the previous study Laurencia papillosa, Laurencia liophor, and Laurencia paniculata. Wrangelia penicillata was recorded on the beaches of Benghazi and Tocra. Comparing the current study with the previous study on Tocra Beach revealed that the same species was recorded in the current study, and it is the only species. This is not surprising, as only one species of the genus Wrangelia has been recorded in Mediterranean countries.